2018
DOI: 10.2306/scienceasia1513-1874.2018.44s.011
|View full text |Cite
|
Sign up to set email alerts
|

Translational cancer research towards Thailand 4.0

Abstract: Cancer is still a major cause of mortality in the Thai population. The heterogeneity and complexity of cancer make this disease often result in ineffective treatment and a fatal outcome. Primary prevention for a knownrisk cancer is one way to minimize the number of new cancer cases; however, effective treatment with reasonable cost-effectiveness is important for cancer patients. Basic and preclinical cancer research are necessary for better and deeper understanding of the nature of cancer. Several research ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, the study of HMGN3 in cancers has not yet been reported. Cholangiocarcinoma (CCA), a cancer of bile duct epithelium, is high prevalence in Northeastern Thailand [11]. Liver fluke (Opisthorchis viverrini; Ov) infection is a major risk factor that induces chronic inflammation and stimulates inflammatory cytokine secretion, such as transforming growth factor β (TGF-β) and interleukin-6 (IL6) [12,13], leading to malignant transformation of bile duct cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of HMGN3 in cancers has not yet been reported. Cholangiocarcinoma (CCA), a cancer of bile duct epithelium, is high prevalence in Northeastern Thailand [11]. Liver fluke (Opisthorchis viverrini; Ov) infection is a major risk factor that induces chronic inflammation and stimulates inflammatory cytokine secretion, such as transforming growth factor β (TGF-β) and interleukin-6 (IL6) [12,13], leading to malignant transformation of bile duct cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, lung cancer ranked second in mortality rate among Thai males, preceded by liver cancer in 2015. Lung cancer has high incidence in the north (especially the three provinces: Chiang Mai, Lampang and Lamphun) while liver cancer is extremely high in the north-east [2,3]. Based on the most recent volume of the Cancer in Thailand, the annual age-standardized incidence rates per 100 000 (for the years 2013-2015) of lung cancer for males and females, respectively, were 32.1 and 21.6 in Chiang Mai, 32.9 and 19.5 in Lampang and 37.9, and 19.8 in Lamphun [3].…”
Section: Introductionmentioning
confidence: 99%